Depoliticizing the United Nations Human Rights Council: Mixed Membership for a Brighter Future - Lemay, Sarah (2013)
The United Nations charter-based human rights apparatus has long been plagued by concerns of politicization. This pervasive issue first brought the demise of the United Nations Commission on Human Rights in 2006 and led to the creation of an entirely new entity, the United Nations Human Rights Council, in the hope of answering the concerns of the international community. Although major reforms were undertaken, politicization is now once again cited as one of the main issues of the new Council. In this essay, we identify the source of politicization as the intergovernmental nature of these human rights bodies, and suggest that mitigation of this issue is possible through the reform of the Council’s membership. The creation of a mixed expert-state body will allow for a more functional, depoliticized body in the protection and promotion of human rights.